Tubarão and Seu Lázaro's dog: Spectacular and banal violence in a Brazilian favela. (September 2019) - Ben Penglase, R.
This article re-examines ethnographic research I conducted on violence and insecurity in a favela in Rio de Janeiro, Brazil. It examines how the ethnographic strategies I chose – both methodologically and representationally – were shaped by different forms of violence. Contrasting a spectacular incident of violence, where a drug-dealer shot a person and a neighborhood dog, with more banal and everyday forms of violence, I ask how my ethnographic approach shaped my anthropology, or analysis, of violence. I argue that my focus on more spectacular types of violence was shaped by three factors: my own methodological and political positioning, the relationship between some forms of violence and narration, and the trope of the everyday state of emergency. These factors, though, tend to obscure ethnographic attention to more banal forms of violence. I argue that a deeper understanding of violence can be produced by paying equal attention to more banal forms of deprivation, but that this analysis requires a different ethnographic approach.